ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi pada Sekretariat Daerah Kabupaten Pati) - Bayu Dwi Asmara, 11.42.02.0021 (Students Journal of Accounting and Banking, 2013)
This study aimed to determine the effect of leadership style on job satisfaction, career development influence on job satisfaction, leadership style influence on performance, career development influences the performance and the effect of job satisfaction on the performance of the District Secretariat Pati. The analysis tool used is multiple regression, while the questionnaire is used as a data collector. Measurements using a Likert scale of 7 (seven) alternative answers. The research was conducted at the Office of the Regional Secretariat Pati which has a population of 227 employees. Respondents were obtained through purposive sampling criteria that employees have a minimum education level D3 to limit tenure > 3 years and obtained total sample of 111 employees. Based on the analysis of this study concluded that: leadership style has positive and significant impact on job satisfaction, career development, and a significant positive effect on job satisfaction, leadership style has positive and significant effect on employee performance, career development, and a significant positive effect on employee performance, job satisfaction positive and significant effect on employee performance, while mediation tests proved that the variable job satisfaction mediates leadership styles on employee performance, as well as career development on employee performance. Keywords: leadership styles, career development, job satisfaction and employee performance.